Involvement and Trust in a Brand as Predictors of Loyalty Categories - Licen Indahwati Darsono (Universitas Islam Indonesia, 2007)
Customer loyalty is the most valuable asset for the firm. Several researchs find that customer loyalty is positively related with profitability. The purpose of this research is to investigate the power of involvement and trust in a brand (as cognitive and conative antece-dent of loyalty) to predict loyalty categories. Dick and Basu (1994) conceptualization of loyaly is used as the main reference in this research. The object of this research is facial whitening product, and the subjects are women. Data is collected in two central locations in Yogyakarta. The finding of this research indi-cates that involvement and trust in a brand has a contribution to predict loyalty categories, such as loyal, latent loyalty, spurious loyal, and no loyalty. The results also support that trust in a brand has more important contribution to predict loyalty categories. Keywords: involvement, trust in a brand, relative attitude, repeat patronage